Improving The Ability To Recognize Number Symbols Using Flashcard In Group A Children At Islahul Ummah Kindergarten In The 2024/2025 Academic Year - Hilyani, Hilyani; Jannah, Rauhun; Muhajirin, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2025)
Abstract. This reserach aims to improve the ability to recognize numerical symbols using flash cards in group A children at TK Islahul Ummah. The research was conducted at TK Islahul Ummah, located in Dusun Cupek, Sigar Penjalin Village, Tanjung Subdistrict, North Lombok Regency. The study focused on 23 group A children who were in the process of learning to recognize numerical symbols. This research is a classroom action study using the model developed by Kemmis & Mc.Taggart. Data collection methods included observation, documentation, and testing. The data analysis technique used was descriptive quantitative analysis.The results of the study showed an improvement in the ability to recognize numerical symbols through the use of flash cards among group A children. In the pre-cycle stage, 10 children (43.47%) achieved mastery. This increased in the first cycle, with 15 children (65.21%) achieving mastery. In the second cycle, the results showed a further improvement in the children's ability to recognize numerical symbols. This was evidenced by 20 children achieving the "developing as expected" and "developing very well" categories, with a classical completeness score of 86.95%. The use of flash cards proved effective in enhancing children's ability to recognize numerical symbols.